Investigation on occurrence states of CO2 storage in formations with gas field produced water reinjection - YANG Shugang, REN Jinman, CAI Mingyu, LIU Haotong, LIU Shuangxing, XUE Ming, ZHANG Kunfeng (Youqicang pingjia yu kaifa)
Under the background of synergistic pollution and carbon reduction, gas field produced water reinjection coupled with CO2 geological storage provides an important pathway to promote synergistic efficiency and expand the benefits of CO2 geological storage. The evolution of CO2 occurrence states in formations with gas field produced water reinjection directly affects the CO2 storage efficiency and long-term security. Based on the interaction mechanism of CO2, gas field produced water, and reservoir rocks, the PHREEQC software was employed to systematically investigate the influence patterns and underlying mechanisms of CO2 pressure, produced water salinity, reservoir rock type, and formation temperature on the two CO2 occurrence states: dissolved-mineralized phase and free phase. Combined with changes in mineral composition and dissolution-mineralization ratios during reactions, the dominant factors affecting CO2 occurrence states in formations with gas field produced water reinjection were analyzed. The results showed that: (1) Feldspar and chlorite served as the primary minerals promoting CO2 mineralization reactions, while illite and calcite functioned as the main carbon fixation minerals. (2) The amount of CO2 in the dissolved-mineralized phase (hereinafter referred to as CO2 dissolution-mineralization quantity) increased with higher CO2 pressure but decreased with increasing salinity of gas field produced water. In sandstone systems, the CO2 dissolution-mineralization quantity decreased with increasing temperature, while in limestone systems, it first decreased and then increased with increasing temperature. (3) Under simulation conditions, changes in CO2 pressure led to variations in CO2 dissolution-mineralization proportions ranging from 47% to 72% in sandstone and limestone systems. Differences in rock type led to variations in CO2 dissolution-mineralization proportions ranging from 10% to 45%. Changes in produced water salinity and formation temperature led to variations in CO2 dissolution-mineralization proportions ranging from 2%-31% and 3%-15%, respectively, in sandstone and limestone systems. These findings are significant for deepening the understanding of CO2 occurrence state evolution and influencing factors, and for advancing the practical demonstration of gas field produced water reinjection coupled with CO2 geological storage from theoretical research to field applications.